Voltage mode control for buck converter - Thandayithabani, Maran Pillai (2012)
This project is about the study, design and a practical implementation of voltage mode control of buck converter. Buck converter is a stepdown switch mode power supply where its output voltage is always less than the input voltage. UC3573 is used in this project as a PWM control IC where it provides pulse signal to the gate terminal of the MOSFET. The output voltage of buck converter is changed when there is changing in the input voltage and/or the load. To cater the problem, voltage mode control (VMC) scheme is applied in this project. This controller has a simple hardware implementation and flexibility. PSpice simulations are performed before hardware implementation. A prototype buck converter with voltage mode control is built on printed circuit board (PCB). The prototype buck converter maintains the output voltage when there is changing in the input voltage and/or the load.